Strategy, information processing and scorecard models in the UK financial services sector - Judith Broady-Preston; Tim Hayward (Information Research: An International Electronic Journal)
In the current turbulent business environment, quality information is required to ensure that companies achieve competitive advantage by using such information to make decisions more rapidly than their rivals. Scorecard models are employed increasingly to translate the mission and strategy of a company into a comprehensive set of performance measures, providing the framework for a strategic management system. Presented here are the results of a British Library Research and Innovation Centre funded project which examined the role of information in the strategic management of UK retail banks. All the banks surveyed used scorecard models of some description, principally to ease blockages in information flow. Information gathering and analysis activities were perceived as necessary elements of the work of all managers, especially when viewed in conjunction with the trend towards bottom-up strategy formulation in companies.